Anti-windup control for nonlinear singularly perturbed switched systems with actuator saturation. Issue 10 (27th July 2018) - Zhou, Linna; Wang, Congcong; Wang, Qianjin; Yang, Chunyu
ABSTRACT: This paper considers the problem of anti-windup (AW) control for nonlinear singularly perturbed switched systems with actuator saturation. An AW controller consisting of a dynamic state feedback (DSF) controller and an AW compensator is firstly constructed. Then, two methods are proposed to determine the AW controller gain matrices by a common Lyapunov function. One of which assumes that the singular perturbation parameter ϵ is available and designs ϵ -dependent AW controller gains simultaneously. The other one, which considers the case that ϵ is unknown but sufficiently small, designs the ϵ -independent DSF controller gain matrices first and then designs the ϵ -independent AW compensator gain matrices. Both of the methods are reduced to solving convex optimisation problems and can achieve larger stability bound and basin of attraction than the existing results. Finally, examples are used to illustrate the feasibility and advantages of the proposed methods.